The Inhibitory Effect of Scutellaria baicalensis Extract and Its Active Compound, Baicalin, on the Translocation of the Androgen Receptor with Implications for Preventing Androgenetic Alopecia - Kim, Ah-Reum; Kim, Su-Na; Jung, In-Keun; Kim, Hyun-Hee; Park, Young-Ho; Park, Won-Seok (Planta Medica, 2014)
Androgens affect several human skin and prostate functions, and the androgen receptor is crucial for regulating the androgen-related mechanisms. In this study, we assessed the antagonizing effects of a Scutellaria baicalensis extract and its main component baicalin on proliferation of human scalp dermal papilla cells. First, the extract and baicalin slightly dissociated the radioisotope-labeled androgen receptor-agonist complex in the androgen receptor binding assay, and the IC50 values were measured to assess the androgen receptor antagonistic effect of the extract (93 µg/mL) and baicalin (54.1 µM). Second, the extract and baicalin treatments dose-dependently inhibited the overgrowth of LNCaP prostate cancer cells, which were stimulated by dihydrotestosterone. Third, the extract and baicalin inhibited nuclear translocation of the androgen receptor stimulated by dihydrotestosterone in human dermal papilla cells. Additionally, the extract and baicalin enhanced proliferation of human dermal papilla cells in vitro. These results show that the extract and baicalin inhibited androgen activation signaling and promoted hDPC proliferation, suggesting that they could be used as active ingredients for treating androgen-associated disorders, such as androgenetic alopecia.
Keywords: baicalin; Scutellaria baicalensis; Lamiaceae; dihydrotestosterone; androgen receptor; androgen antagonism; androgenetic alopecia